Effectiveness of Education Program on Nurse-Midwife’s Knowledge Regarding Immediate Newborn Care in Delivery Rooms at Maternity Hospitals in Baghdad City/Iraq - Wafaa Adnan Hussein; Iqbal Majeed Abbas (Institute of Medico-legal Publications Pvt Ltd, 2021)
Immediate newborn care is the care given to newborns in the transitional period (immediately after birth)which crucial to their survival. Nurses- midwives require adequate knowledge and skills to provideimmediate newborn care. The study was aimed at determining the effectiveness of education program onnurses- midwives’ knowledge before and after the implementation of an educational program regardingimmediate newborn care in delivery room among study sample. Quasi-experimental study was conductedfrom 1st October 2019 to 20th January 2021 at three maternity teaching hospitals in Baghdad city/Al-RussafaHealth Directorate: Al-Elwiya Maternity Teaching hospital, Fatema Al- Zahra Maternity and PediatricHospital, Al- Za’faraniyah General Hospital. Non-probability (convenient sample) used to collect the datafrom (40) participant (nurse-midwife) who work in delivery room that considered as study sample. Theresults of study indicated that nurses– midwives’ knowledge assessment before the implementation of aneducational program for study sample was moderate related to immediate newborn care in delivery room.There were high significant differences in participants’ knowledge at pretest and posttest before and afterthe implementation of education program for study sample. Socio- demographic and professional variablewere no significant effect on their knowledge. The study findings showed that program had been an effectivemethod of increasing the nurses- midwives’ knowledge about immediate newborn care in delivery room.